Justice Souter and the Civil Rules - Scott Dodson (Washington University Law Review, 2010)
On April 30, 2009, after almost twenty years on the U.S. Supreme Court, Justice David Hackett Souter announced his retirement. A quiet personality never comfortable in the D.C. spotlight (except, perhaps,during his confirmation hearings), Justice Souter was rarely characterized as a force on the Court. No doubt his legacy will be marked in large part — and perhaps unfairly — by his membership in the Planned Parenthood of Southeastern Pennsylv ania v. Casey troika and his apparent Blackmun-like slide while on the Court from conservative to liberal (at least, as relative to the Court as a whole). Despite his momentous contribution to Casey and the role that that case has played, we ought to be wary of remembering Justice Souter only as a co-author of that single case, a Republican disappointment, or a liberal savior. He did, after all, write 326 opinions while on the Supreme Court (and lent an often crucial vote to hundreds more), including memorable opinions in areas of constitutional criminal law, equal protection, the First Amendment, and federalism. Even in the relatively apolitical world of federal procedure, Justice Souter left an impression. He wrote extensively on the Federal Arbitration Act,voiced thoughtful views on the doctrine of standing,and moved the law forward in the areas of preemption and federal question jurisdiction. We should, therefore, consider more of Justice Souter in commenting on his legacy. I will not attempt a comprehensive look — I leave that for the biographers and Court-watchers. But I will strive to offer a different view of Justice Souter, one that is itself admittedly narrow, but at least is outside of the proverbial defining moments and thus provides, perhaps, an enriching perspective. I focus on Justice Souter‘s views on the federal civil rules.
Keywords: Souter; David H.; 1939-; Civil Procedure; Supreme Court justices (United States)